Impact of the COVID-19 pandemic on violence exposure and alcohol use among adults who drink alcohol. - Akua O Gyamerah; Alexandrea E Dunham; Janet Ikeda; Andy C Canizares; Willi McFarland; Erin C Wilson; Glenn-Milo Santos (PLoS ONE)
The COVID-19 pandemic has exacerbated prevalence of alcohol use and violence, including gender-based violence (GBV); however, little is understood about the pandemic's impact on the relationship between the two. Data were collected from January 2021-April 2023 with adults who drink alcohol (N = 565) in the San Francisco Bay Area. Questions assessed prevalence of heavy alcohol use (≥4 drinks on one occasion ≥4 times a month) in the past 3 months and violence/GBV exposure before and during the pandemic. Logistic regression examined associations between violence and alcohol use. Overall, participants reported heavy alcohol use (73.7%), strong desire for alcohol (53.3%), ever experiencing violence (71.6%), and GBV (20.5%). During the pandemic, participants reported experiencing violence (26.1%), more violence than usual (13.8%), GBV (8.9%), and drinking more alcohol (43.7%). People who experienced violence during the pandemic had significantly greater odds of reporting heavy alcohol use (OR = 1.76, p = 0.05) and drinking more during the pandemic than usual (OR = 2.04, p<0.01). Those who reported experiencing more violence during the pandemic than usual had significantly greater odds of reporting heavy alcohol use (OR = 2.32, p = 0.04) and drinking more during the pandemic (OR = 2.23, p<0.01). People who experienced GBV during the pandemic reported a significantly stronger desire for alcohol (OR = 2.44; p = 0.02) than those not exposed. Alcohol-related harms increased over the COVID-19 pandemic, including increased violence/GBV, alcohol use, and an elevated desire to use alcohol among those who experienced violence during the pandemic. Future pandemic preparedness efforts must prioritize violence prevention strategies and adapt alcohol harm reduction, recovery, and treatment programs to pandemic conditions.